Development of Working Blades From a Titanium Alloy for the Last Steps of a Low Pressure Cylinder for Powerful Steam Turbines - Sherfedinov, Riza; Ishchenko, Mykhailo; Slaston, Liubov; Svitlana, Alyokhina (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The main design studies of JSC “Turboatom” are highlighted when creating a working blade made of titanium alloy with an active part length of 1200 mm for the last stages of K-1000-60/3000 turbines. It is noted that complex calculations for blades made of titanium alloy for the last stages of the low-pressure cylinder of powerful steam turbines are an urgent task. A three-dimensional calculation of the strength of these blades was carried out, the stress-strain state and displacements at different values of the natural frequency of the blade were determined. The calculation of the bladed disk of the stage of the low pressure cylinder is performed. The dynamic frequencies of natural vibrations are determined for various rotation frequencies of the turbine rotor. A feature of manufacturing technology that provides for the control assembly on the process disk is indicated. The blades made of titanium alloy manufactured by JSC “Turboatom”, considered in this work, are successfully operated on K-1000-60/3000 turbines of the South Ukrainian and Khmelnitsky nuclear power plants.